Analysis Of Social Support And Workload With Burnout Among Health Workers At Hospital X - Ferrita Aisya Karyono; Pipit Festi Wiyanarti; Ansarul Fahrudda; Mirrah Samiyah (Global Journal of Health Administration, 2025)
Objective: This study aimed to analyze the relationship between social support, workload, and burnout among inpatient nurses at Hospital X Methods: This study employed a cross-sectional design conducted from December 2024 to May 2025 at Hospital X. The population consisted of 69 inpatient nurses, with a sample of 59 nurses selected using simple random sampling. Data were collected using self-administered questionnaires measuring social support was assessed using a Sarafino-based instrument consisting of emotional support, informational support, instrumental support, appreciative support. Workload using a Budiasa-adapted questionnaire, consisting of work target, working conditions, use of working time, and work standards. Burnout using the Maslach Burnout Inventory consisting emotional exhaustion, depersonalization, and reduced personal accomplishment. Data analysis included descriptive statistics, normality testing, and multiple linear regression with a significance level of α is 0.05. Results: The results showed that nurses experienced moderate levels of social support (mean=31.29), workload (mean=21.22), and burnout (mean=14.98). Multiple regression analysis revealed that social support had a significant negative effect on burnout (B=−0.151, p=0.010), indicating its protective role. In contrast, workload had a significant positive effect on burnout (B = 0.400, p < 0.001), identifying workload as a major risk factor. The regression model explained 33% of the variance in burnout. Conclusion: Social support significantly reduces burnout, while workload significantly increases burnout among inpatient nurses. Strengthening workplace social support and implementing effective workload management are essential strategies to mitigate burnout and improve nurses’ well-being and service quality at Hospital X.